ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA LEMBAGA KEUANGAN PERBANKAN DI BURSA EFEK INDONESIA - Mak Sum (STIE 'INDONESIA' Pontianak, 2014)
This study aimed to determine the relationship between financial performance and stock price. Financial performance consisting of CAR, NPL, ROA, NIM, BOPO and LDR as independent variables have unexpected influence on the stock price as the dependent variable. The sample in this study was 16 banking companies listed in Indonesia Stock Exchange with the observation period 2007 until 2011. The results showed that the variable CAR, NPL, ROA, NIM and BOPO have an influence on the stock price with a significance level = 0.000, respectively, 0.013, 0.021,0.00 and 0.000, whereas the LDR variables have an influence on the stock price with a significant level of 10%. The coefficient of determination shows the contribution of influence on the stock price of 63.1%, while 36.9% are not influenced by other variables examined. Most dominant influence is changing BOPO, CAR and NIM.